ABILITY AS AN IMPORTANT PSYCHOLOGICAL CHARACTERISTIC OF A PERSON - Jumaboyeva Gulasal Oybek qizi (American Journals, 2023)
This article discusses the psychological characteristics of ability, the structure of ability, its types, qualitative and quantitative description of ability, and who dealt with the problem of ability.
Keywords: Ability, activity, qualitative and quantitative indicators, mind, mental goals, concept of ability, psychological phenomenon, levels of ability, psychological characteristics.